Governing the global climate commons: The political economy of state and local action, after the U.S. flip-flop on the Paris Agreement. (July 2018) - Cooper, Mark
Abstract: United States withdrawal from the Paris Agreement, which follows well-known principles of common pool resource management, poses a serious challenge, but it could provide a golden opportunity to cement and advance the efficacy and legitimacy of the Agreement. The Agreement encourages subnational units to participate in a polycentric, multistakeholder governance structure. As many as two dozen states have policies that could put them in compliance. These states represents over 40% of U.S. emissions, making them the 4th or 5th largest emitter. Subnational compliance would give the Agreement a major boost particularly if they seek observer status and are exempted from sanction. Even without such rewards, the states have strong reasons to follow this path. As non-fossil fuel producing states, they have clear interests in developing local resources as the basis for their electricity sector. As a large group, they gain economies of scale and network effects. As part of the American Federalist system, they would be defending their right of independent action. At COP 23, the U.S. subnational entities played a prominent role and the treaty participants reacted strongly against the Trump administration position, while embracing the activities of U.S. subnational entities. The U.S. presence was limited and isolated. Highlights: U.S. withdrawal from the Paris Agreement is an opportunity to build its legitimacy. States likely to be in compliance are 40% of U.S. emissions despite the withdrawal. Compliant states have strong economic and political reasons to seek observer status. COP 23 participants reacted forcefully to reject the Trump administrations complaints. Subnational entities have ramped up their participation.